George Gallup in Hollywood - Ohmer, Susan (Film and culture., 2006)
George Gallup in Hollywood is a fascinating look at the film industry's use of opinion polling in the 1930s and '40s. George Gallup's polling techniques first achieved fame when he accurately predicted that Franklin D. Roosevelt would be reelected president in 1936. Gallup had devised an extremely effective sampling method that took households from all income brackets into account, and Hollywood studio executives quickly pounced on the value of Gallup's research. Soon he was gauging reactions to stars and scripts for RKO Pictures, David O. Selznick, and Walt Disney and taking the public's temperature on Orson Welles and Desi Arnaz, couples such as Fred Astaire and Ginger Rogers, and films like Gone with the Wind, Dumbo, and Fantasia. Through interviews and extensive research, Susan Ohmer traces Gallup's groundbreaking intellectual and methodological developments, examining his comprehensive approach to market research from his early education in the advertising industry to his later work in Hollywood. The results of his opinion polls offer a fascinating glimpse at the class and gender differences of the time as well as popular sentiment toward social and political issues.